Comparative study of some flavor components of coconut vinegar and "Paombong" vinegar - Villamor, Cynthia A.; Aquino, Clarissa G. (1990)
Coconut vinegar was used produced using the "let alone" process in demi-john jars of 5-gallon capacity. he sugared coconut water (18° Brix) yielded alcoholic liquor of 6.16 % alcohol content (20°C). Further fermentation and aging of the coconut liquor produced vinegar with 3.24% total acidity. The physico-chemical changes during fermentation and aging of coconut vinegar was also monitored. The quality of coconut vinegar (C.V) produced in the laboratory was determined relative to the standard vinegar (S.V), arbitrarily chosen to be "Paombong" vinegar. The vinegar quality was measured in terms of sensory characteristics (using Quantitative Descriptive Analysis) and flavor composition (using Gas Chromatography). The C.V. was found to be less sour, sharp, fruity and sweetish but more fatty and spirituous than "Paombong" vinegar in terms of smell. Relative to taste, the C.V. from the standard were not statistically significant. Moreover, comparison of the gas chromatographic chromatograms of coconut and Paombong showed that C.V. was almost the same as that of "Paombong" vinegar in flavor composition. C.V. also contained the 4 acids, 6 esters, 5 alcohols and 2 carbonyls which the "Paombong" vinegar had. From the results of QDA and gas chromatography, C.V. was found to have characteristics very similar to "Paombong" vinegar. The results indicate C.V. has potentials comparable to a high-quality vinegar. Improvement in the fermentation process will make the flavor quality of coconut vinegar come closer to that of the standard vinegar.
Thesis (M.S.F.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Vinegar